Differential Effects of Kupffer Cell Inactivation on Inflammation and The Liver Sieve Following Caecal-Ligation and Puncture-Induced Sepsis in Mice. Issue 4 (April 2017) - Gaddam, Ravinder Reddy; Fraser, Robin; Badiei, Alireza; Chambers, Stephen; Cogger, Victoria C.; Le Couteur, David G.; Bhatia, Madhav
Abstract : ABSTRACT: Sepsis remains a common clinical problem with significant mortality. Activation of the Kupffer cells during sepsis is associated with systemic inflammatory response and multiple organ failure. Kupffer cell activation also leads to structural changes in the liver sinusoidal endothelial cells (LSECs) during endotoxemia. However, these effects remain to be elucidated in caecal-ligation and puncture (CLP)-induced polymicrobial sepsis. To investigate the role of Kupffer cells on LSECs fenestrae and inflammation during CLP-induced sepsis, sepsis was induced by CLP and mice were treated with gadolinium chloride (GdCl3 ) before CLP-induced sepsis, to inactivate Kupffer cells. Mice were sacrificed after 8 h. Blood, liver, and lung tissues were collected and processed to measure LSECs fenestration, myeloperoxidase (MPO) activity, alanine transaminase (ALT) and aspartate aminotransferase (AST) activity, histological examination, and various cytokines/chemokines levels. LSECs fenestrae was studied using scanning electron micrographs of the LSECs. Strikingly, CLP mice treated with GdCl3 were protected against liver injury as evidenced by decreased LSECs defenestration and damage, MPO, ALT and AST activities, liver tissue damage, and inflammatory cytokines TNF-α, IL-6 and IL-1β, and chemokines MCP-1 and MIP-2α. However, CLP mice treated with GdCl3 had no protection against increased lung MPO activity, tissue damage, inflammatory cytokines, and chemokines. Treatment with GdCl3 also had no effect on the systemic inflammatory response as shown by no change in the circulatory inflammatory cytokines and chemokines following CLP-induced sepsis. Collectively, these data suggest that inactivation of Kupffer cells by GdCl3 protects the liver but had no effect on lung injury or inflammation and systemic inflammatory response following CLP-induced sepsis.